Metal ion-activated molecular receptors for aromatic anions with receptor cavities formed from 1- or 2-naphthyloxy moieties appended to cyclen - Smith, C.; Buntine, Mark; Lincoln, S.; Wainwright, K. (The Royal Society of Chemistry, 2003)
Studies of two newly synthesised, isomeric metal ion-activated molecular receptors, [Cd(1,4,7,10-tetrakis{(S)-(−)-2-hydroxy-3-(1′-naphthyloxy)propyl}-1,4,7,10-tetraazacyclododecane)](ClO4)2•H2O and [Cd(1,4,7,10-tetrakis{(S)-(−)-2-hydroxy-3-(2′-naphthyloxy)propyl}-1,4,7,10-tetraazacyclododecane)](ClO4)2, show that both act as molecular receptors for the p-toluenesulfonate anion. The binding cavity depths for the two receptors were calculated from ab initio molecular modelling to be 4.81 and 7.27 Å, respectively. Despite the smaller cavity depth for the first receptor, it forms the more stable inclusion complexes, as assessed by the relative magnitude of the decrease in electrical conductivity and 13C NMR spectral changes. This indicates that hydrogen bonds, from the hydroxyl hydrogen-bond donors at the base of the receptor cavity, rather than π interactions between the aromatic walls of the cavity and the included p-toluenesulfonate are principally responsible for its retention. Nonetheless, the hydrophobic character of the aromatic-binding cavity walls may play a major kinetic role in the formation of the inclusion complexes.